Utility of hematological and iron-related screening in elite athletes - Fallon, K. (Clinical Journal of Sport Medicine, 2004)
Objective: To determine the clinical and performance related utility of hematological and iron-related screening in elite athletes. Design: Prospective cohort study. Setting: The Department of Sports Medicine at the Australian Institute of Sport. Participants: Male and female elite athletes undergoing routine medical screening over a period of 2 to 3 years. Intervention: Blood testing for hematological and iron-related biochemical variables. Measures: White blood cell count, red blood cell count, hemoglobin, hematocrit, mean cell volume, mean cell hemoglobin concentration, platelet count, percent hypochromic red cells, serum iron, ferritin, transferrin, and percent transferrin saturation. Results: Eight female athletes (4.6%) had clinically relevant abnormal results, 6 with an obvious explanation on clinical history and examination and 1 who was diagnosed with hemochromatosis following genetic testing. Eighty-nine (51.1%) female athletes had abnormal results that were not associated with obvious clinical signs or symptoms. Twenty-seven female athletes had a serum ferritin less than 30 ng/mL and were placed on iron supplementation. In male athletes, 5 cases had screening abnormalities that were associated with illness or other factors identified during the clinical consultations. Nonclinically significant abnormalities in males were generally minor reductions in hemoglobin and/or hematocrit or minor alterations in red cell parameters. Five male athletes had a serum ferritin less than 30 ng/mL and were placed on iron supplementation. Conclusion: Screening for hematological and iron-related abnormalities in male athletes has a very low yield. Due to the critical nature of the effects of anemia and low serum ferritin on some aspects of performance, it is reasonable to perform a full blood count and a serum ferritin on male athletes entering an elite training program. Further testing should be performed on clinical grounds. In females, the yield is greater. Again, it is reasonable to perform a full blood count and a serum ferritin on female athletes entering an elite training program. In view of their greater risk of iron depletion and to assess the effect of increased training inherent in elite programs, this could be repeated at 6-month intervals, or an isolated measurement of serum ferritin could be performed. Further testing should be performed on clinical grounds.